Rate of digestion of foods and postprandial glycaemia in normal and diabetic subjects. Issue 6232 (5th July 1980) - Jenkins, D J; Wolever, T M; Taylor, R H; Ghafari, H; Jenkins, A L; Barker, H; Jenkins, M J
Abstract : Carbohydrate portions (2 g) of lentils, soya beans, and wholemeal bread were incubated for three hours with human digestive juices and the effect of digestibility on blood glucose examined. Lentils and soya beans released only 39% and 8% respectively of the sugars and oligosaccharides liberated from bread. In healthy volunteers 50 g carbohydrate portions of cooked lentils and soya beans raised blood glucose concentrations by only 42% (p < 0.001) and 14% (p < 0.001) of the bread value. There was a similar response in diabetics. These results suggest that rate of digestion might be a important factor determining the rise in blood glucose concentration after a meal and that supplementing chemical analysis with in-vitro and in-vivo food testing might permit identification of especially useful foods for diabetics.